Analysis of Key Safety Metrics of Thorium Utilization in LWRs. (1st May 2016) - Ade, Brian; Worrall, Andrew; Powers, Jeffrey; Bowman, Steve
Abstract: Thorium has great potential to stretch nuclear fuel reserves because of its natural abundance and because it is possible to breed the 232 Th isotope into a fissile fuel ( 233 U). Various scenarios exist for utilization of thorium in the nuclear fuel cycle, including use in different nuclear reactor types (e.g., light water, high-temperature gas-cooled, fast spectrum sodium, and molten salt reactors), along with use in advanced accelerator-driven systems and even in fission-fusion hybrid systems. The most likely near-term application of thorium in the United States is in currently operating light water reactors (LWRs). This use is primarily based on concepts that mix thorium with uranium (UO2 + ThO2 ) or that add fertile thorium (ThO2 ) fuel pins to typical LWR fuel assemblies. Utilization of mixed fuel assemblies (PuO2 + ThO2 ) is also possible. The addition of thorium to currently operating LWRs would result in a number of different phenomenological impacts to the nuclear fuel. Thorium and its irradiation products have different nuclear characteristics from those of uranium and its irradiation products. ThO2, alone or mixed with UO2 fuel, leads to different chemical and physical properties of the fuel. These key reactor safety–related issues have been studied at Oak Ridge National Laboratory and documented in "Safety and Regulatory Issues of the Thorium Fuel Cycle" (NUREG/CR-7176, U.S. Nuclear Regulatory Commission, 2014). Various reactor analyses were performed using the SCALE code system for comparison of key performance parameters of both ThO2 + UO2 and ThO2 + PuO2 against those of UO2 and typical UO2 + PuO2 mixed oxide fuels, including reactivity coefficients and power sharing between surrounding UO2 assemblies and the assembly of interest. The decay heat and radiological source terms for spent fuel after its discharge from the reactor are also presented. Based on this evaluation, potential impacts on safety requirements and identification of knowledge gaps that require additional analysis or research to develop a technical basis for the licensing of thorium fuel are identified.